JIMD Reports, Volume 41 Focus Issue: Adults and Metabolism (JIMD Reports,, 2018)
JIMD Reports publishes case and short research reports in the area of inherited metabolic disorders. Case reports highlight some unusual or previously unrecorded feature relevant to the disorder, or serve as an important reminder of clinical or biochemical features of a Mendelian disorder.